Neonatal and maternal outcome in oligohydramnios: a prospective study - Ahmar, Rizwan; Parween, Sadia; Kumari, Smita; Kumar, Manish (International Journal of Contemporary Pediatrics, 2018)
Background: Oligohydramnios presents a threat to the fetus and has been correlated with increased risk of intrauterine growth retardation, meconium aspiration syndrome, severe birth asphyxia, low APGAR scores and congenital abnormities. It is associated with perinatal morbidity and mortality and maternal morbidity in a significant number of cases. Therefore, early detection of oligohydramnios and its management is important. Aim of this study was to know the fetal and maternal outcome in oligohydramnios. Methods: 90 patients in third trimester of pregnancy with Oligohydramnios were selected after satisfying inclusion and exclusion criteria. A detailed history and examination were done. All required investigation done. Oligohydramnios confirmed by measuring Amniotic fluid index (AFI). Results: Mean maternal age-26.1 years. Incidence of oligohydramnios was more in primipara (64.4%) in our study. And operative morbidity was also more in primipara (51.7%). Most common cause of Oligohydramnios was idiopathic (44.44%). Operative morbidity was significantly higher in Non-reassuring FHR (80%) than reassuring FHR (32%). 7 patients (7.78%) were found with fetoplacental insufficiency on Doppler study. Conclusions: Oligohydramnios is frequent occurrence and demands intensive fetal surveillance and proper antepartum and intrapartum care so that perinatal morbidity and mortality and maternal morbidity can be reduced.